Galactic synchrotron emissivity measurements between 250° < l < 355° from the GLEAM survey with the MWA. Issue 3 (17th November 2016) - Su, H.; Hurley-Walker, N.; Jackson, C. A.; McClure-Griffiths, N. M.; Tingay, S. J.; Hindson, L.; Hancock, P.; Wayth, R. B.; Gaensler, B. M.; Staveley-Smith, L.; Morgan, J.; Johnston-Hollitt, M.; et al.
Abstract : Synchrotron emission pervades the Galactic plane at low radio frequencies, originating from cosmic ray electrons interacting with the Galactic magnetic field. Using a low-frequency radio telescope, the Murchison Widefield Array (MWA), we measure the free–free absorption of this Galactic synchrotron emission by intervening H ii regions along the line of sight. These absorption measurements allow us to calculate the Galactic cosmic ray electron emissivity behind and in front of 47 detected H ii regions in the region 250° < l < 355°, | b | < 2°. We find that all average emissivities between the H ii regions and the Galactic edge along the line of sight (ϵ b ) are in the range of 0.39 ∼ 1.45 K pc −1 with a mean of 0.77 K pc −1 and a variance of 0.14 K pc −1 at 88 MHz. Our best model, the two-circle model, divides the Galactic disc into three regions using two circles centring on the Galactic Centre. It shows a high emissivity region near the Galactic Centre, a low emissivity region near the Galactic edge, and a medium emissivity region between these two regions, contrary to the trend found by previous studies.